Independent work of students - Berezovska, Olga (My University, 2016)
Modem high school is oriented towards Bologna agreement which is aimed at intensive informatisation, mobilization of potential for self-organizing system organization, that provides the self-realization of professional qualities and experience of independent work.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; independent work; students; самостійна робота; студенти; самостоятельная работа; студенты